2020
DOI: 10.1002/adfm.202001564
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation into Dynamic Function of Third Component Incorporated in Ternary Near‐Infrared Nonfullerene Organic Solar Cells

Abstract: Organic solar cells (OSCs) consisting of an ultralow‐bandgap nonfullerene acceptor (NFA) with an optical absorption edge that extends to the near‐infrared (NIR) region are of vital interest to semitransparent and tandem devices. However, huge energy‐loss related to inefficient charge dissociation hinders their further development. The critical issues of charge separation as exemplified in NIR‐NFA OSCs based on the paradigm blend of PTB7–Th donor (D) and IEICO–4F acceptor (A) are revealed here. These studies co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…This decrease in V oc , which is affected by higher dielectric effects in binary configuration, has been experimentally proven in earlier work by Veldman et al [ 170 ] In ternary configurations with enhanced dielectric screening, we mostly see a constant V oc , which deemed the V oc unaffected by the dielectric screening. [ 114,145,147 ] Interestingly, in another article by Duan et al, [ 172 ] they observed an increase in V oc at the optimum ternary ratio when the dielectric screening effects took place. This could be due to the improved CT and CS coupling which promotes enhanced k CT→CS and results in lower nonradiative recombination loss to V oc .…”
Section: Electronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease in V oc , which is affected by higher dielectric effects in binary configuration, has been experimentally proven in earlier work by Veldman et al [ 170 ] In ternary configurations with enhanced dielectric screening, we mostly see a constant V oc , which deemed the V oc unaffected by the dielectric screening. [ 114,145,147 ] Interestingly, in another article by Duan et al, [ 172 ] they observed an increase in V oc at the optimum ternary ratio when the dielectric screening effects took place. This could be due to the improved CT and CS coupling which promotes enhanced k CT→CS and results in lower nonradiative recombination loss to V oc .…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…Most reports showed significant improvement in J sc and FF with enhanced k CT→CS due to the dielectric screening effect. [ 114,145,146,167,169 ] This is quite intuitive considering a better dissociation of charges leads to improved charge mobility and transport. However, as in Equation (), any form of decrease in Δ E CT‐G increases k nr , which is detrimental toward V oc .…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…The dynamics of these TA spectra display two interesting phenomenon: one is that the kinetic decay processes of two ternary blends are faster than that of binary system in the shorter timescale part (<1 ps), which reflects chiefly the hole injection information and can be in good consistence with the results of transient GSB features. [ 53 ] The other is that these TA decays of two ternary blends (especially for the PM6:DRCN5T:BTP‐4Cl film) at the longer temporal delay as seen from 100 ps to 7 ns are slower than the kinetics of binary PM6:BTP‐4Cl film, basically referring to the nature of non‐geminate recombination. [ 54 ] The prolonged lifetime of CS species is in favor of the extraction and collection of the photogenerated charge carriers to promote electricity generation, coinciding well with the higher FFs and more efficient EQE response observed in ternary OSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work has established that a fullerene derivative acceptor would largely enhance electron extraction and reduce charge recombination. [ 48,49 ] Inspired by it, we next used PC 71 BM as a third component in the P75:Y6 binary blend with a P75:Y6:PC 71 BM ratio of 1.5:1.4:0.1, 1.5:1.3:0.2, and 1.5:1.2:0.3 wt% in ternary blends, which are denoted as T 0.1 , T 0.2 , and T 0.3 with respect to PC 71 BM wt%, respectively, for simplicity in the following discussion. The optical absorptions of binary and ternary blend films in comparison with their neat films are shown in Figure 1c.…”
Section: Resultsmentioning
confidence: 99%